2022
DOI: 10.3390/jcm11071907
|View full text |Cite
|
Sign up to set email alerts
|

Visual Tract Degradation in Bilateral Normal-Tension Glaucoma—Cortical Thickness Maps and Volumetric Study of Visual Pathway Areas

Abstract: The aim of the study was to evaluate changes in the central visual pathways during the early and advanced stages of bilateral normal-tension glaucoma (NTG). Methods: The studied groups constituted patients with bilateral normal-tension glaucoma of the same stage (n = 45) and age-matched healthy volunteers (n = 17). All patients underwent ophthalmic examination and examination on a 1.5 Tesla Magnetic Resonance Scanner (Optima 360, GE Healthcare). Volume and cortical thickness analyses were performed using the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… Fujishiro et al (2022) reported that ocular hypertension could lead to reduced cytochrome oxidase expression in the visual cortex. Pankowska et al (2022) found that normal-tension glaucoma patients had reduced thickness in the right lateral occipital gyrus and left lingual gyrus. Consistent with these findings, we observed significantly lower DC values in the right calcarine sulcus in PACG patients, which suggested abnormal functional connectivity within the visual network.…”
Section: Discussionmentioning
confidence: 93%
“… Fujishiro et al (2022) reported that ocular hypertension could lead to reduced cytochrome oxidase expression in the visual cortex. Pankowska et al (2022) found that normal-tension glaucoma patients had reduced thickness in the right lateral occipital gyrus and left lingual gyrus. Consistent with these findings, we observed significantly lower DC values in the right calcarine sulcus in PACG patients, which suggested abnormal functional connectivity within the visual network.…”
Section: Discussionmentioning
confidence: 93%
“… Nuzzi et al (2018) demonstrated that patients with glaucoma showed abnormal FC changes in the visual pathway. In addition, Pankowska et al (2022) reported that the patients with advanced glaucoma showed an increase in the gray matter thickness in the V1 region. Meanwhile, early glaucoma was associated with reduced thickness in the right lateral occipital gyrus and the left lingual gyrus ( Pankowska et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pankowska et al (2022) reported that the patients with advanced glaucoma showed an increase in the gray matter thickness in the V1 region. Meanwhile, early glaucoma was associated with reduced thickness in the right lateral occipital gyrus and the left lingual gyrus ( Pankowska et al, 2022 ). Haykal et al (2022) reported that patients with primary open-angle glaucoma (POAG) showed a loss of both axonal coherence and density in the pregeniculate visual pathways, while the postgeniculate pathways exhibited a loss of axonal coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesize that age-related LGN atrophy may exist in normal subjects, which makes the difference of LGN size between glaucoma and control groups in the older group smaller than that in the younger group. There was a significant difference in LGN volume measured by MRI between the early glaucoma group and the advanced glaucoma group [22,30] . The nasal optic nerve fibers of each eye converges with the temporal nerve fibers of the opposite eye and project to LGN.…”
Section: Discussionmentioning
confidence: 89%